2021
DOI: 10.1007/s40264-021-01121-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile of GSK’s Inactivated Quadrivalent Seasonal Influenza Vaccine in Belgium, Germany and Spain: Passive Enhanced Safety Surveillance Study for the 2019/2020 Influenza Season

Abstract: Introduction Seasonal influenza infects millions annually in Europe. Annual influenza vaccination is the most effective measure to reduce the risk of infection and its complications, especially among young children and older adults. Objective We assessed adverse event (AE) frequency after receiving GSK’s inactivated quadrivalent seasonal influenza vaccine (IIV4). Methods A passive enhanced safety surveillance study was conducted in Belgium, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In Europe, the European Medicines Agency began requiring annual enhanced safety surveillance for seasonal influenza vaccines in 2014 [ 15 ]. Following an initial feasibility study conducted in the 2015–2016 season [ 16 ], surveillance studies have been conducted for IIV4 in England in 2016–2017 [ 17 ] and 2017–2018 [ 18 ], and in Belgium, Germany and Spain in 2018–2019 [ 19 , 20 ], 2019–2020 [ 21 ] and 2020–2021 [ 22 ]. All these surveillance studies reported no safety concerns with IIV4, supporting the acceptable safety profile of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the European Medicines Agency began requiring annual enhanced safety surveillance for seasonal influenza vaccines in 2014 [ 15 ]. Following an initial feasibility study conducted in the 2015–2016 season [ 16 ], surveillance studies have been conducted for IIV4 in England in 2016–2017 [ 17 ] and 2017–2018 [ 18 ], and in Belgium, Germany and Spain in 2018–2019 [ 19 , 20 ], 2019–2020 [ 21 ] and 2020–2021 [ 22 ]. All these surveillance studies reported no safety concerns with IIV4, supporting the acceptable safety profile of the vaccine.…”
Section: Discussionmentioning
confidence: 99%